Ring Shaped DGS Patch Antenna for Wireless Communication (International Journal of Communication Systems and Network Technologies, 2022)
A orbicular microstrip patch antenna (MPA) conceptualizes with negative ground formation defected ground structure (DGS) feed for narrowband (NB) is assigned. The antenna is conceptualized using CST Studio executing in the Frequency spectrum of operation from 2 GHz to 2.8 GHz. The antenna has a condensed structure with measurements of 60 × 60 × 1.6mm3, transformed as a ring hole and grounded defected ground structure. The assigned antenna can achieve a gain of 5.53 dBi at a frequency of 2.4 GHz and a maximum of 6.57 dB. The power efficiency of the antenna is superior, reaching 97%, and the voltage standing wave ratio (VSWR) is about 1.26 in the narrowband frequency range. The bandwidth, size and robust electrical peculiarities of this antenna make it accomplish for narrow-band implementations.
Keywords: Rectangular Patch Antenna; Ring Shaped; DGS; Wireless Communication; 2.4 Ghz Frequency Band